PENGARUH INOVASI PRODUK DAN MODAL TERHADAP DAYA SAING PADA USAHA MIKRO, KECIL DAN MENENGAH (UMKM) MOLEN DI TAWANGMANGU - Sapelege, Yedi Kristian; Prakoso, Yusak (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
This study aims to analyze the influence of product innovation and capital on the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) using mixers (Micro, Small, and Medium Enterprises) in Tawangmangu. MSMEs play a crucial role in the national economy, but often face challenges such as limited capital and low product innovation. The research method used a quantitative approach with a census sampling technique of 45 MSMEs using mixers (Micro, Small, and Medium Enterprises) in Tawangmangu. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS 16. The results showed that product innovation had a positive but insignificant effect on competitiveness (β=0.107; p=0.070), while capital had a positive and significant effect (β=0.886; p=0.000). Simultaneously, both variables contributed 94.1% to competitiveness. These findings indicate that capital is the dominant factor in increasing the competitiveness of MSMEs using mixers, while product innovation needs to be consistently improved. This study provides practical implications for MSMEs in strengthening their business capital and optimizing product innovation to compete in the market.